The Relationship between Peer Social Support and Resilience Attitudes in Regional Students in Makassar City - Akbar, Surya Algazali; Fakhri, Nurfitriany; Piara, Muh Rajan (Polteknik Ilmu Pemasyarakatan, 2024)
Regional Students are a group of students who leave their hometown and will stay in an area for a certain period of time. Due to the differences in various aspects of life, regional students are expected to be able to adapt to their host environment. Regional Students who have successfully adapted during the overseas period will display resilient behavior when going through critical periods full of pressure and challenges. The aim of this research is to determine the relationship between peer social support and the resilience attitudes of regional students in the city of Makassar. The participant of this research were 300 regional students in the city of Makassar. The scales used in this research are the Social Support Behavior SS-B and the Ego Resiliency Scale Revised ER 89-R. The sampling technique uses a non-probability sampling technique, namely convenience sampling. The analysis in this research used SPSS for Windows version 24. Hypothesis testing was carried out using Sperman Rank analysis with the results of an r-value of 0.266 and a p-value of 0.00 < 0.05, which means it is significant. This means that the higher the peer social support for regional students in the city of Makassar, the better the attitude of resilience among Regional Students. The implications of this research provide an overview of the relationship between peer social support and resilience among regional students in the city of Makassar and become the basis for universities to run a peer group program with the aim of getting students actively involved in both regional students and non-migrant students in the city of Makassar